2023
DOI: 10.1108/ijppm-06-2022-0284
|View full text |Cite
|
Sign up to set email alerts
|

Climate change adaptation strategies and technical efficiency of maize producers in Benin, West Africa

Abstract: PurposeThis study aims to discuss climate change, by modifying the timing of several agricultural operations, reduce the efficiency and yield of inputs leading to a lower production level. The reduction of the effects of climate change on production yields and on farmers' technical efficiency (TE) requires the adoption of adaptation strategies. This paper analyses the impact of climate change adaptation strategies adopted on maize farmers' TE in Benin.Design/methodology/approachThis paper uses an endogeneity-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(189 reference statements)
0
1
0
Order By: Relevance
“…Flood disasters mostly occur in places with dense populations, large agricultural impact areas, concentrated rivers and lakes, and plentiful rainfall, such as the temperate and subtropical regions of the northern hemisphere [ 3 ]. Previous studies have revealed that natural disasters hinder agricultural productivity growth, as production in this sector is dependent on the present climatic and biophysical conditions [ 1 , [4] , [5] , [6] ]. Natural disasters mainly damage crops and livestock and lead subsequently to crop failure and a reduction in producers' income [ 1 , [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%
“…Flood disasters mostly occur in places with dense populations, large agricultural impact areas, concentrated rivers and lakes, and plentiful rainfall, such as the temperate and subtropical regions of the northern hemisphere [ 3 ]. Previous studies have revealed that natural disasters hinder agricultural productivity growth, as production in this sector is dependent on the present climatic and biophysical conditions [ 1 , [4] , [5] , [6] ]. Natural disasters mainly damage crops and livestock and lead subsequently to crop failure and a reduction in producers' income [ 1 , [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%